Pengembangan Media Pembelajaran Interaktif Berbasis Komputer bagi Guru - Sinar Sinurat (PT. Ndruru Jaya Mandiri, 2026)
This community service activity aims to improve teachers’ competencies in developing computer-based interactive learning media to support innovative, effective, and engaging learning processes. The main problem faced by partner schools is the limited ability of teachers to utilize digital technology as instructional media and the lack of experience in designing interactive teaching materials. The implementation methods included needs analysis, planning, training, hands-on practice, mentoring, and evaluation. The training focused on the use of computer applications to create interactive presentations, instructional videos, and digital teaching materials that align with classroom learning needs. The results indicated a significant improvement in teachers’ understanding and skills in designing computer-based learning media. Teachers were able to produce learning media that could be directly implemented in the teaching and learning process. Furthermore, the use of interactive media increased students’ motivation, engagement, and participation during classroom activities. This activity had a positive impact on improving learning quality and enhancing teachers’ creativity in utilizing educational technology. Therefore, similar programs should be conducted continuously to support digital transformation in education and strengthen teachers’ professionalism in responding to the challenges of 21st-century learning.